Preparação e caracterização de filmes de gelatina e amido de batata transesterificado com ácidos graxos - Ribeiro, Bruna de Sousa (2020)
The present study had as a guiding principle the development of films based on natural polymers. Bearing in mind that the current trend gains support in the production and development of renewable, available, biocompatible, non-toxic and low-cost materials. In this study, we opted for the polymeric polysaccharide-protein combination, for which potato starch (AN) and gelatin (GL) were used. The AN was modified by transesterification with fatty acids in organic solvent, so that the films were then prepared. The product obtained from the transesterification reaction, called transesterified starch (AT), was investigated by FT-IR, MEV, DRX, TG-DTG and wetting contact angle analysis. These analyzes corroborated the occurrence of the transesterification reaction, since absorption bands of the ester group were identified in the FT-IR spectrum, especially carbonyl (C = O) with intense stretching in 1742 cm-1 . In addition, SEM images showed that the shape of the starch granule was altered, indicating the disruption of the crystalline structure and the formation of an amorphous structure, being corroborated by XRD diffractograms. The lower thermal stability (TG) of the transesterified starch (AT) in the second degradation stage is also an indication of change in the starch structure, given that the interactions of the hydroxyl groups of glucose in the starch are stronger than the interactions of the group ester in the AT. Changes in surface polarity were observed in the wetting contact angle analysis, suggesting that after the transesterification reaction the starch became less hydrophilic. As for the AT-GL films, they were prepared using the casting technique, and plasticized using 25 % w/w glycerol. Three filmogenic formulations were investigated from the variation of the components AT-GL: 4:1, 1:1 and 1:4. The films were characterized by their surface wettability, microstructural, morphological, thermal properties and the possible interactions between the components of the polymeric matrix. The hydrophilicity and heterogeneity of the films were directly proportional to the gelatin content. The FT-IR showed the interactions that occurred between transesterified starch, gelatin and glycerol, portrayed by the bands at 2920, 2850, 1742, 1634, 1548 and 1242 cm-1 . TG analysis indicated a thermally stable structure up to 100 °C. Therefore, the data obtained suggest that AT-GL films are compatible and can be used in applications of biocompatible polymers.